Leiomyosarcoma Ex Pleomorphic Adenoma of the Parotid Gland: A Case Report and Literature Review - Michael Coulter; Jingxuan Liu; Mark Marzouk (Case Reports in Otolaryngology)
There is only one previously reported incident in the English literature of sarcoma ex pleomorphic adenoma of the parotid and there are only 8 cases of primary parotid leiomyosarcoma. In our case, a 79-year-old female patient presented to our care with left preauricular pain, swelling, and facial weakness. After CT imaging, she underwent left total parotidectomy. A spindle cell lesion was identified intraoperatively and the facial nerve was sacrificed. Subsequent analysis of the lesion yielded a diagnosis of leiomyosarcoma ex pleomorphic adenoma. After 30 fractions of radiation therapy, scans were negative for tumor. However, 18 months after first experiencing symptoms, she was found to have metastases to the brainstem and lung. When diagnosing sarcoma ex pleomorphic adenoma of the parotid gland, it is important to perform thorough immunohistochemical staining and exclude a previous history of sarcoma or other sources of metastases. Complete resection is critical due to the tumor’s local aggressiveness and metastatic potential. Although these tumors are not very responsive to chemotherapy or radiation, adjuvant treatment is commonly used when margins are unclear.